Urgensi Interaksi Edukatif dan Definisi Kelompok Belajar dalam Pendidikan - Candra Kirana (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2022)
This study aims to determine the concept of educative interaction & the definition of learning groups in education and the importance of this method used in education & teaching. The method in this study emphasizes the type of library research obtained from books related to the definition of educational interaction, group learning, its characteristics and urgency in education & teaching. Data analysis used the analytical technique proposed by Miles and Huberman with the stages of data reduction, data presentation and conclusion drawing (verification). The results of the study show that educational interaction is said to be successful in learning if an educator is able to understand the characteristics of students. Failure to create a conducive educative interaction begins with the emergence of the educator's lack of understanding of the characteristics of students. Furthermore, in each teaching, the teacher should try to create a social atmosphere that evokes cooperation among students in receiving lessons so that teaching is carried out more effectively and efficiently.